2015
DOI: 10.1021/acs.est.5b00631
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the Fate of Mercury in the Fish and Bottom Sediments of Minamata Bay, Japan, Using Stable Mercury Isotopes

Abstract: Between 1932 and 1968, industrial wastewater containing methylmercury (MeHg) and other mercury (Hg) compounds was discharged directly into Minamata Bay, Japan, seriously contaminating the fishery. Thousands of people who consumed tainted fish and shellfish developed a neurological disorder now known as Minamata disease. Concentrations of total mercury (THg) in recent fish and sediment samples from Minamata Bay remain higher than those in other Japanese coastal waters, and elevated concentrations of THg in sedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 45 publications
7
45
3
2
Order By: Relevance
“…This approach has been used to estimate the δ 202 Hg of MMHg prior to photodegradation ("pre-photodegraded MMHg") in previous studies (e.g., [51][52][53][54]60 to +0.8‰), [51][52][53]60 where it was suggested that IHg in sediment is biotically methylated (−MDF) 26,27 followed by significant mer-mediated biotic degradation (+MDF) 24 , such that the residual MMHg has higher δ 202 Hg than the sediment (net positive biotic MDF). 51 …”
Section: Linking Ihg Sources To Mmhgmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has been used to estimate the δ 202 Hg of MMHg prior to photodegradation ("pre-photodegraded MMHg") in previous studies (e.g., [51][52][53][54]60 to +0.8‰), [51][52][53]60 where it was suggested that IHg in sediment is biotically methylated (−MDF) 26,27 followed by significant mer-mediated biotic degradation (+MDF) 24 , such that the residual MMHg has higher δ 202 Hg than the sediment (net positive biotic MDF). 51 …”
Section: Linking Ihg Sources To Mmhgmentioning
confidence: 99%
“…42,44 This study, combined with the results of our previous work in the Yuba River, 42 42 This result contrasted with lower δ 202 Hg in IHg compared to MMHg (+MDF from IHg to MMHg) that was previously observed in lakes, estuaries and the coastal ocean. [51][52][53][54] In Cache Creek and Yolo Bypass, sediment is thought to be an important source of IHg that can be methylated, leading to MMHg bioaccumulation in local food webs. 11,14 Based on previous studies in a variety of aquatic environments, hypothesized that in this study the MDF relationship between IHg and MMHg in Cache Creek would be consistent with the Yuba River, whereas the MDF between IHg and MMHg in Yolo Bypass wetlands would be more similar to that previously reported in lakes and the coastal ocean.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the stable mercury isotope data, Balogh et al (2015) suggested that methylmercury was produced in bottom sediments of Minamata Bay and entered the food web, possibly from sediment porewaters or near the sediment-water interface. Irukayama et al (1964b) surveyed the horizontal and vertical distributions of total mercury in the sediment in Minamata Bay in October 1963 and compared the results obtained by Kitamura et al (1960b) in 1959 (Fig.…”
Section: Bioindicators Of Mercury Pollutionmentioning
confidence: 99%
“…The Shin Nippon Chisso Fertilizer Company started its production of acetaldehyde in Minamata in 1932, yet only 24 years later the first cases of Minamata disease were diagnosed (Balogh et al, 2015). In the Minamata accident, due to the biomagnification, (marginal) harm increased over time.…”
Section: Figure 7: Liability and Biomagnificationmentioning
confidence: 99%